Diversity of reptiles of the semi-deciduous forest in Buena Vista, Remedios, Villaclara: new localities for Cuba - Rodríguez-González, Alejandro Michel (2023)
Living reptiles are easy to recognize with the naked eye, however, they are difficult to define due to the morphological heterogeneity and phylogenetic complexity of the group. The objective of this research is to determine the species of reptiles found in the semi-deciduous forest located in the town of Buena Vista, municipality of Remedios, province of Villa Clara, Cuba. For the development of the research, the following capture methods were used: capture by means of a rod with a sliding knot, capture by hand, by means of a terrestrial trap with a diversion fence in combination with pit (boat) and cylinder traps, opportunistic collection, visual encounter, limited time collection and capture by means of thick leashes. Site visits were conducted from April 2022 to April 2023, covering all seasons of the year. As a result of the field work in situ, 19 species of reptiles belonging to four families were detected in the study area, which constitute new localities for Cuba, with 63.2% of endemism. The presence of Arrhyton doluchura (Werner, 1909), which is in the vulnerable category, according to the Red Book of Cuban vertebrates, was detected in the study area.